EFFECTS OF EMPLOYEE MOTIVATION STRATEDIES ON EMPLOYEE PERFORMANCE IN TELECOMMUNICATION COMPANIES IN SOMALIA - Yusuf, Mohamed Abdirizak Sh; GICHINGA, LUCY (IJRDO - Journal of Business Management, 2016)
Motivation plays an important role in all public and private organizations. Without motivatingtheir employees organizations can’t run and can’t achieve their goals. Motivation andperformance of the employees are essential tools for the success of any organization in thelong run. On the one hand, measuring performance is critical to organization’s management,as it highlights the evolution and achievement of the organization. On the other hand, there isa positive relationship between employee motivation and organizational effectiveness,reflected in numerous studies. This research aims to analyze the drivers of employee motivationto high levels of organizational performance. The literature shows that factors such asempowerment and recognition increase employee motivation. If the empowerment andrecognition of employees is increased, their motivation to work was also improve, as well astheir accomplishments and the organizational performance. Nevertheless, employeedissatisfactions caused by boring jobs and pressure from clients, might weaken theorganizational performance. The Purpose of this study is to explore the effect of motivation onemployee’s performance of telecommunication companies in Somalia. The study has thefollowing objectives; to assess the extent to which financial incentives influences employeeperformance. To assess the extent to which training and development influences employeeperformance, to determine the effect of employee empowerment on employee performance. Thestudy was utilized descriptive research design in order to describe the variables of the study.The target population of this study was 5000 and sample size of 98. The Data was being collected used structured questionnaire as a research instrument. The data was being analyzedusing percentages, frequencies, graphs and regression analysis with the help of StatisticalPackage for Social Science (SPSS version 22). Respondents agree on financial incentivesaffects employee performance. The respondents agreed that the bonuses and extras addedyearly to my salary make me feel satisfied. The study sought to establish the effects Trainingand Development on employee performance of telecommunication companies in MogadishuSomalia From the findings respondents agreed in our organization training motivatesemployees to be more committed towards organizational goals and also results are consistentwith the findings obtained on training has helped me in improving my overall required skillsfor work . The respondent also agreed I believe that my set targets and objective are attainedand identified by the firm through training program in the company. Employee empowermenteffects on employee performance of telecommunication companies. Respondents agreed that Ihave total freedom to decide how to accomplish my work. The results and findings indicatedthat Human Resource Management should come up with an effective performancemeasurement system that rewards hard workers and penalizes ineffective workers. Theresearcher recommends that all employees should be motivated to ensure they areretained and this will improve performance. In this way overall organizational productivityand effectiveness can be enhanced.